Hubungan Sleep Hygiene dengan Kualitas Tidur Pada Remaja Kelas XII di SMAN 1 Tanah Putih - Yulia Febrianita; Rita Anyalina; Lora Marlita (Universitas Pahlawan Tuanku Tambusai, 2026)
Sleep hygiene activities play an important role in supporting normal sleep needs. Therefore, every individual should practice proper sleep hygiene regularly to achieve healthy and normal sleep patterns. Globally, insufficient sleep has become a common issue among adolescents. The World Health Organization (WHO) reports that nearly 30% of adolescents worldwide experience sleep disturbances such as insomnia and circadian rhythm disorders. In the United States, a survey conducted by the National Sleep Foundation (2020) found that 72.7% of adolescents reported sleeping less than eight hours per night on school days, which is below the minimum recommended duration. The purpose of this study was to determine the relationship between sleep hygiene and sleep quality among 12th-grade students at SMAN 1 Tanah Putih. The sampling technique used in this study was random sampling, with a total of 109 respondents. The research instrument used was a questionnaire. The results of the study on sleep hygiene showed that 7 respondents (6%) had good sleep hygiene, 66 respondents (61%) had moderate sleep hygiene, and 36 respondents (33%) had poor sleep hygiene. The results of the quantitative analysis on sleep quality revealed that 13 respondents (11.9%) had good sleep quality, while 96 respondents (88.1%) had poor sleep quality. The Chi-square test showed a p-value of 0.031, which is less than the significance level of 0.05. This finding indicates that there is a significant relationship between sleep hygiene and sleep quality among 12th-grade students at SMAN 1 Tanah Putih. It is recommended that 12th-grade students at SMAN 1 Tanah Putih increase their awareness of the importance of maintaining proper sleep hygiene to improve their overall sleep quality.